Peningkatan Hasil Belajar Teks Prosedur Menggunakan Studi Kasus di Kelas VIII Madrasyah Tsanawiyah Al-Hakimiyah Paringgonan Tahun 2024-2025 - Hanifah Parapat (PANTAK: Jurnal Penelitian Tindakan Kelas, 2025)
This study aims to improve the learning outcomes of procedural texts through the application of the case study method to eighth grade students of Madrasyah Tsanawiyah Al-Hakimiyah Paringgonan in the 2024–2025 academic year. This study is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 30 students consisting of 20 female students and 10 male students. Data collection techniques used tests, observation, and documentation. The results showed an increase in the average class score from 65 in the pre-action to 72 in cycle I and 82 in cycle II. The percentage of learning completeness increased from 40% to 87%, thus achieving classical completeness. In addition to improving learning outcomes, the case study method also increases students' activeness and systematic thinking skills. Thus, the case study method is effective in improving the learning outcomes of eighth grade students' procedural texts.